Importation and circulation of poliovirus in Bulgaria in 2001 - Kojouharova Mira; L.F. Zuber Patrick; Gyurova Snejana; Fiore Lucia; Buttinelli Gabriele; Kunchev Angel; Vladimirova Nadejda; Korsun Neli; Filipova Radosveta; Boneva Roumiana; Gavrilin Eugene; Deshpande Jagadish M.; et al. (The World Health Organization, 2003)
OBJECTIVE: To characterize the circumstances in which poliomyelitis occurred among three children in Bulgaria during 2001 and to describe the public health response. METHODS: Bulgarian authorities investigated the three cases of polio and their contacts, conducted faecal and serological screening of children from high-risk groups, implemented enhanced surveillance for acute flaccid paralysis, and conducted supplemental immunization activities. FINDINGS: The three cases of polio studied had not been vaccinated and lived in socioeconomically deprived areas of two cities. Four Roma children from the Bourgas district had antibody titres to serotype 1 poliovirus only, and wild type 1 virus was isolated from the faeces of two asymptomatic Roma children in the Bourgas and Sofia districts. Poliovirus isolates were related genetically and represented a single evolutionary lineage; genomic sequences were less than 90% identical to poliovirus strains isolated previously in Europe, but 98.3% similar to a strain isolated in India in 2000. No cases or wild virus isolates were found after supplemental immunization activities were launched in May 2001. CONCLUSIONS: In Bulgaria, an imported poliovirus was able to circulate for two to five months among minority populations. Surveillance data strongly suggest that wild poliovirus circulation ceased shortly after supplemental immunization activities with oral poliovirus vaccine were conducted.